2022
DOI: 10.1155/2022/1558860
|View full text |Cite
|
Sign up to set email alerts
|

Metadichol®: A Novel Nanolipid Formulation That Inhibits SARS-CoV-2 and a Multitude of Pathological Viruses In Vitro

Abstract: Increasing outbreaks of new pathogenic viruses have promoted the exploration of novel alternatives to time-consuming vaccines. Thus, it is necessary to develop a universal approach to halt the spread of new and unknown viruses as they are discovered. One such promising approach is to target lipid membranes, which are common to all viruses and bacteria. The ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has reaffirmed the importance of interactions between the virus envelope and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Additionally, Metadichol has been found to modulate the expression of genes involved in viral infections (60) and inhibit the entry of SARS-CoV-2 into host cells, indicating its potential role in antiviral responses. Moreover, the ability of metadichol to induce the expression of critical transcription factors such as Yamanaka factors (61) in various cell types holds promise for its application in stem cell therapy and reprogramming of somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Metadichol has been found to modulate the expression of genes involved in viral infections (60) and inhibit the entry of SARS-CoV-2 into host cells, indicating its potential role in antiviral responses. Moreover, the ability of metadichol to induce the expression of critical transcription factors such as Yamanaka factors (61) in various cell types holds promise for its application in stem cell therapy and reprogramming of somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another telomerase activator, metadichol (CAS RN 1627854-29-8), has been used to defeat organ failure by enriching cells with telomerase. 336 Another study reported that natural formulations including Centella asiatica extract (08AGTLF) comprising >95% triterpenes, Astragalus extract, TA-65, oleanolic acid (CAS RN 508-02-1), maslinic acid (CAS RN 4373-41-5), and certain multinutrient formulations trigger significant increase in telomerase activity. 337 4.4.…”
Section: Antiaging Drugsmentioning
confidence: 99%
“…Preliminary experimental data suggested that TA-65 (cycloastragenol, CAS RN 78574-94-4), an extract of Astragalus membranaceus roots, can perform as a telomerase activator, but so far no sound clinical data have been reported. Another telomerase activator, metadichol (CAS RN 1627854-29-8), has been used to defeat organ failure by enriching cells with telomerase . Another study reported that natural formulations including Centella asiatica extract (08AGTLF) comprising >95% triterpenes, Astragalus extract, TA-65, oleanolic acid (CAS RN 508-02-1), maslinic acid (CAS RN 4373-41-5), and certain multinutrient formulations trigger significant increase in telomerase activity …”
Section: Antiaging Drugsmentioning
confidence: 99%
“…Evidence has suggested that the reactivation of telomerase expression by using a gene therapy approach is the best example of the lifespan extension of mice and delay aging without cancer occurrence [ 73 ]. A recent study has found that Metadichol, a telomerase activator, is used to overcome organ failure by enriching cells with telomerase and is a safer alternative [ 74 ]. Another study explained that natural compounds such as 08AGTLF (Centella asiatica), Nutrient 4 ( Astragalus ), TA-65 ( Astragalus membranaceus ), OA (oleanolic acid), and MA (maslinic acid); and Nutrients 1, 2, and 3 have telomerase activation, and among all, 08AGTLF has the greatest potential to activate telomerase [ 75 ].…”
Section: Telomere Reactivationmentioning
confidence: 99%